2018
DOI: 10.1089/end.2017.0455
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Video Endoscopic Inguinal Lymphadenectomy Through a Hypogastric vs Leg Subcutaneous Approach for Penile Cancer

Abstract: Hypogastric approach is as effective and safe as VEIL-L for penile cancer. Moreover, VEIL-H can avoid the operation on both the limb and abdomen if laparoscopic pelvic lymphadenectomy is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
0
11
0
4
Order By: Relevance
“…Comparing these methods, prophylactic lymphadenectomy has the best overall survival benefit from early resection of occult metastasis 11,12. However, concurrent complications related to lymph drainage and wound healing are relatively high despite surgical modifications 1315. Therefore, accurate inguinal LNM prediction could pinpoint patients who are the best candidates for inguinal lymphadenectomy, which could not only achieve the best survival rate for patients with occult metastasis but also avoid unnecessary treatment for patients with a low risk of developing LNM.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing these methods, prophylactic lymphadenectomy has the best overall survival benefit from early resection of occult metastasis 11,12. However, concurrent complications related to lymph drainage and wound healing are relatively high despite surgical modifications 1315. Therefore, accurate inguinal LNM prediction could pinpoint patients who are the best candidates for inguinal lymphadenectomy, which could not only achieve the best survival rate for patients with occult metastasis but also avoid unnecessary treatment for patients with a low risk of developing LNM.…”
Section: Introductionmentioning
confidence: 99%
“…[37] In addition, we also demonstrated that video endoscopic inguinal lymphadenectomy via a hypogastric subcutaneous approach was safe and effective, and it could avoid the operation on both the limb and abdomen if simultaneous laparoscopic pelvic lymphadenectomy was required. [38]…”
Section: Discussionmentioning
confidence: 99%
“…23 Outra forma de diminuir a morbilidade é a realização da LIMVA bilateral em simultâneo por duas equipas cirúrgicas distintas, variante técnica descrita por Pompeo et al em 2013. 10 Apesar do potencial mostrado pela LIMVA, outras técnicas minimamente invasivas têm surgido, nomeadamente a LIMVA robótica 24 e a abordagem por via abdominal/hipogástrica, 25 com resultados comparáveis à LIMVA.…”
Section: Discussionunclassified